Common variants at VRK2 and TCF4 conferring risk of schizophrenia - Steinberg, Stacy; de Jong, Simone; Andreassen, Ole A.; Werge, Thomas; Børglum, Anders D.; Mors, Ole; Mortensen, Preben B.; Gustafsson, Omar; Costas, Javier; Pietiläinen, Olli P. H.; Demontis, Ditte; Papiol, Sergi; et al. (Human molecular genetics, 2011)
Common sequence variants have recently joined rare structural polymorphisms as genetic factors with strong evidence for association with schizophrenia. Here we extend our previous genome-wide association study and meta-analysis (totalling 7 946 cases and 19 036 controls) by examining an expanded set of variants using an enlarged follow-up sample (up to 10 260 cases and 23 500 controls). In addition to previously reported alleles in the major histocompatibility complex region, near neurogranin (NRGN) and in an intron of transcription factor 4 (TCF4), we find two novel variants showing genome-wide significant association: rs2312147[C], upstream of vaccinia-related kinase 2 (VRK2) [odds ratio (OR) = 1.09, P = 1.9 × 10−9] and rs4309482[A], between coiled-coiled domain containing 68 (CCDC68) and TCF4, about 400 kb from the previously described risk allele, but not accounted for by its association (OR = 1.09, P = 7.8 × 10−9).